2012
DOI: 10.1037/a0027517
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hands-on child sexual offenses among possessors of Internet child pornography.

Abstract: The recent Supreme Court ruling in U.S. v. Comstock (2010) upheld the constitutionality of The Adam Walsh Act, which provides for civil commitment of child pornography (CP) offenders certified as sexually dangerous, thereby approving litigation of all such prisoners in the federal system. The two studies reported here sought to address the question: What is the likelihood that an individual convicted of child pornography offenses has a prior history of a hands-on sexual offense involving a child or has a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
0
24
0
4
Order By: Relevance
“…A substantial rise in convictions for CSEM-related offences (Radford et al, 2011) has consequently resulted in an increase in research on CSEMOs (Babchishin, Hanson, & Hermann, 2011;Babchishin, Hanson & VanZuylen, 2015;Seto, Hanson, & Babchishin, 2011). One of the most widely researched questions is whether CSEMOs are a distinct type of sex offender from contact sex offenders (CSOs) and comparison studies have identified some differences regarding psychological and offence-related variables Elliott, Beech, & Mandeville-Norden, 2012;Lee, Li, Lamade, Schuler, & Prentky, 2012;McCarthy, 2010). However, CSEMOs do not present as a homogeneous group: CSEM use has been linked to a range of functions beyond sexual satisfaction, such as financial gain or using the material to desensitise a potential contact victim (Caple, 2008;Quayle, Erooga, Wright, Taylor, & Harbinson, 2006;Seto, Reeves, & Jung, 2010;Surjadi, Bullens, Van Horn, & Bogaerts, 2010;Taylor, Holland, & Quayle, 2001;Taylor & Quayle, 2003, 2005, and research on the offence motivations of CSEMOs has revealed a range of motivators for viewing CSEM, such as a sexual interest in children, indiscriminate sexual interests, or unmet emotional needs Seto et al, 2010).…”
Section: The Emergence Of Non-contact Sex Offending As a Research Areamentioning
confidence: 99%
“…A substantial rise in convictions for CSEM-related offences (Radford et al, 2011) has consequently resulted in an increase in research on CSEMOs (Babchishin, Hanson, & Hermann, 2011;Babchishin, Hanson & VanZuylen, 2015;Seto, Hanson, & Babchishin, 2011). One of the most widely researched questions is whether CSEMOs are a distinct type of sex offender from contact sex offenders (CSOs) and comparison studies have identified some differences regarding psychological and offence-related variables Elliott, Beech, & Mandeville-Norden, 2012;Lee, Li, Lamade, Schuler, & Prentky, 2012;McCarthy, 2010). However, CSEMOs do not present as a homogeneous group: CSEM use has been linked to a range of functions beyond sexual satisfaction, such as financial gain or using the material to desensitise a potential contact victim (Caple, 2008;Quayle, Erooga, Wright, Taylor, & Harbinson, 2006;Seto, Reeves, & Jung, 2010;Surjadi, Bullens, Van Horn, & Bogaerts, 2010;Taylor, Holland, & Quayle, 2001;Taylor & Quayle, 2003, 2005, and research on the offence motivations of CSEMOs has revealed a range of motivators for viewing CSEM, such as a sexual interest in children, indiscriminate sexual interests, or unmet emotional needs Seto et al, 2010).…”
Section: The Emergence Of Non-contact Sex Offending As a Research Areamentioning
confidence: 99%
“…Ein Vergleich von Internettätern (n = 113), Handson-Tätern (n = 176) und Tätern, die in beiden Bereichen delinquierten ("mixed offenders") (n = 60), zeigte, dass sich die drei Gruppen bezüglich antisozialer Verhaltensweisen und Beschäftigung mit dem Internet unterschieden, dass ein höherer Score bei "Beschäftigung mit dem Internet" die Zugehörigkeit zur Gruppe der Internettäter wahrscheinlicher machte, während zusätzlich hohe Werte auf einer Skala "antisoziale Verhaltensweisen" ein guter Prädiktor für die Zugehörigkeit zu der Gruppe der "mixed offenders" war (Lee et al 2012).…”
Section: Konsummotivation Und Kognitionenunclassified
“…The consistent differentiating factor is antisociality, with contact offenders being significantly more antisocial (Eke et al, 2011;Seto and Eke, 2005;Webb et al, 2007;Lee et al, 2012). Internet sex offenders also appear to be less deviant, less physically aggressive and less impulsive than contact offenders (Tomak et al, 2009).…”
Section: Internet Sex Offendersmentioning
confidence: 83%